8 - La RSE stratégique dans le secteur minier au Sénégal : incubateur d’inclusion de genre et de développement communautaire ? - Doucouré, Bakary (Africa Development, 2023)
So-called strategic corporate social/societal responsibility (CSR) is an increasingly popular approach in some socio-professional networks in Senegal, including in the mining and extractive sector. This article raises the question of whether this type of CSR promotes, particularly at the local/community level, gender inclusion on the one hand and development on the other. The analysis, based on empirical cases, shows a mixed contribution of strategic CSR initiatives to the achievement of gender equality/equity and development at the community level. Among the main causes of this observation, there are the limits in the dialogue and consultation/inclusion process, the limited duration of most initiatives and of their capacity to produce lasting effects and impacts, prejudices and stereotypes in the distribution of sex and gender roles, etc.